Making the End as Good as the Beginning: Financial Planning and Retirement for Women Plastic Surgeons. Issue 4 (October 2016) - Johnson, Debra J.; Shenaq, Deana; Thakor, Manisha
Abstract : Summary: Financial planning is critically important to ensure financial security both during a plastic surgical career and in retirement. Unfortunately, plastic surgery training includes very little in the way of financial planning. The information that is available in the literature is mostly geared toward men. Women, with longer lifespans and more family care responsibilities, have unique needs when it comes to financial planning. Adequate attention must also be paid to life after retirement. A plastic surgical career can be all-encompassing, and thus women need to carefully plan volunteer activities, new hobbies, and even a second career to make their retirement years fulfilling and enjoyable. Key points regarding financial planning during the various phases of a woman plastic surgeon's career are discussed. Options for retirement are presented.